Etoricoxib for generalized osteoarthritis. Case report - I. S. Dydykina; P. S. Kovalenko; D. M. Kudinsky (Современная ревматология)
The article discusses the treatment of patients with primary generalized osteoarthritis (OA), a common joint lesion of different localization. Clinical guidelines are presented that provide guidance on various drug and non-drug approaches in the treatment of primary generalized OA. In accordance with the modern understanding of the pathogenesis of OA, the role of inflammation and the influence of various pro-inflammatory factors, the priority of anti-inflammatory therapy, primarily non-steroidal anti-inflammatory drugs (NSAIDs), is justified. A clinical case of a 5-year observation of a patient with primary generalized OA and low compliance to treatment with symptom-modifying slowacting drugs is described. For articular syndrome exacerbations etoricoxib (Kostarox®) was mainly used as an analgesic and anti-inflammatory agent at a dose of 60 mg / day for 7–14 days with a good effect. Due to self-isolation and inability to visit a doctor during COVID-19 pandemic, the patient took etoricoxib for a long time (up to 200 days) for severe neck- and backpain relief, the duration of some courses was up to3 months. We discuss the possibility of etoricoxib use not only in the «on demand» mode, but also for a long time – until the effect is achieved.